The Operational Activities of EU Banking Groups and the Portfolio of Government Bonds during the COVID-19 Pandemic – the Case of Non-euro Area EU Countries - Koleśnik, Jan (Comparative Economic Research. Central and Eastern Europe, 2025)
The objective of this article is to present the results of an analysis of how the form of activities of EU banking groups affected their decisions to purchase non-euro area EU government bonds during the COVID-19 pandemic. The dataset consists of the portfolios of government bonds (including both on- and off-balance sheet items) issued by non-euro area EU countries held by 93 EU banking groups (data aggregated at the highest group level). For each country surveyed, we analysed the structure of banks purchasing the bonds issued by that country and its evolution between 2019 and 2022, with purchasers broken down into domestic banks and EU banking groups operating in the relevant market through subsidiaries or branches. The analysis shows that, during the COVID-19 pandemic, the decisions to purchase the government bonds of non-euro area EU countries were primarily determined by the operational activities of these groups in the local markets. However, significant similarities were observed within the three country groups identified. The added value of the analysis is that it provides insights into the resilience of these banking groups against the ‘moral suasion’ exerted by non-euro area EU countries to purchase their government bonds. Notably, domestic banking groups exhibited the least resistance to this moral suasion, as evidenced by their increasing share of a specific issuer’s government bonds within the portfolio held by all EU banking groups across nearly all surveyed countries.